Advances in surgical treatment of lymphedema - Beederman, Maureen; Chang, David W. (Archives of Plastic Surgery, 2021)
An estimated 250 million people worldwide suffer from lymphedema. In the past, the firstline option for treatment was nonsurgical management, either in the form of compression garments or wrapping, or comprehensive decongestive therapy, with debulking surgery reserved for the more advanced cases. However, with improvements in microsurgical techniques and imaging modalities, surgical intervention is increasingly being utilized. This review highlights recent advancements in the surgical treatment of lymphedema, specifically focusing on improvements in imaging, surgical techniques, and prevention of lymphedema.
Keywords: Lymphedema; Surgery; Microsurgery; Advances; Treatment